ESBC: an enhanced modular multilevel converter with H-bridge front end - Amankwah, Emmanuel; Costabeber, Alessando; Jasim, Omar; Trainer, David; Clare, Jon C. (2017)
This paper presents the Enhanced Series Bridge Converter (ESBC), a hybrid modular multilevel converter with H-bridge front end suitable for high power grid applications. It retains the advantages of other modular multilevel topologies while offering compact structure, making it attractive for offshore stations, back-back HVDC stations, and city centre infeeds. The structure, operating principles and energy management of the converter are discussed. Simulation results from a scaled down medium voltage demonstrator are presented to validate the concept.